Cidade, poder e diferença: outros caminhos para a compreensão do direito à cidade sustentável em Henri Lefebvre - Silva, Diego Coimbra Barcelos da (My University, 2018)
This dissertation aims at analyzing and proposing alternative ways of understanding the right to a sustainable city, in the light of power relations. To do so, it seeks to explore some key assumptions and concepts of Henri Lefebvre's work, mostly those on which the original proposal of the right to the city was built, in order to match with the categories of analysis in the development of the research. In this attempt, outlines a systematic argumentative framework, that points to the redistribution of power in the urban space, the full exercise of multiterritoriality and multiple territories and the participationintervention in the production of environmental and legal-urban discourse, the latter through the legal pluralism. Also seeks to analyze the theoretical feasibility of the proposed meanings within the scope of Lefebvrian spatial theory.
Este trabalho monográfico tem por objeto a análise e a proposição de caminhos alternativos para a compreensão do direito à cidade sustentável, sob o prisma das relações de poder. Para tanto, busca esquadrinhar alguns pressupostos e conceitos centrais da obra de Henri Lefebvre, notadamente aqueles em que a proposta original do direito à cidade se alicerça, a fim de compatibilizá-los com as categorias de análise necessárias à condução da pesquisa. Nesse intento, esboça um quadro argumentativo sistemático que aponta para as direções da redistribuição do poder no espaço urbano, da plenitude do exercício da multiterritorialidade e dos múltiplos territórios e da participaçãointervenção na produção dos discursos ambiental e jurídico-urbanístico, este último através do pluralismo jurídico. Busca, ainda, analisar a viabilidade teórica dos sentidos propostos no escopo da teoria espacial lefebvriana.
Keywords: Direito municipal; Divisões territoriais e administrativas; Sustentabilidade; Municipal corporations; Administrative and political divisions; Sustainability